2000
DOI: 10.1211/0022357001777667
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anti-metastatic Activity of Pentoxifylline by Encapsulation in Conventional Liposomes and Sterically Stabilized Liposomes in Murine Experimental B16F10 Melanoma Model

Abstract: Pentoxifylline has been shown to exhibit anti-metastatic activity by inhibiting homing of B16F10 melanoma cells in the murine experimental metastasis model. In this study, the effect of encapsulation of pentoxifylline in conventional and sterically stabilized liposomes on its anti-metastatic activity in the murine experimental metastasis model was investigated. After a single intravenous dose (10, 20 or 40 mg kg(-1)), pentoxifylline solution, as well as conventional pentoxifylline liposomes, significantly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…18) In the present study, the NF-κB inhibitors PTX, NAC, and ASP showed protective effects in our in vivo lung metastasis model. PTX, widely used as a hemorheological agent in the treatment of peripheral vascular disease, was earlier shown to suppress lung metastasis formation by B16F10 melanoma 19,20) and NAC, a chemopreventive agent that acts through a variety of mechanisms, 21) inhibits VEGF production in human melanoma cell lines, 22) invasion of endothelial cells, 23) and invasion of human bladder cancer cells through the suppression of MMP-9. 24) ASP has been demonstrated to inhibit angiogenesis, 25) invasion and metastasis of EBV-associated tumors, 26) and HGF-induced invasiveness of HepG2 human hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…18) In the present study, the NF-κB inhibitors PTX, NAC, and ASP showed protective effects in our in vivo lung metastasis model. PTX, widely used as a hemorheological agent in the treatment of peripheral vascular disease, was earlier shown to suppress lung metastasis formation by B16F10 melanoma 19,20) and NAC, a chemopreventive agent that acts through a variety of mechanisms, 21) inhibits VEGF production in human melanoma cell lines, 22) invasion of endothelial cells, 23) and invasion of human bladder cancer cells through the suppression of MMP-9. 24) ASP has been demonstrated to inhibit angiogenesis, 25) invasion and metastasis of EBV-associated tumors, 26) and HGF-induced invasiveness of HepG2 human hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pretreatment method describes the situation in which a patient is detected with primary tumor and receives chemotherapy, while the post-treatment method entails a situation in which metastasis has already been detected and then chemotherapy has started. Furthermore, liposomal pentoxifyline and niosomal cisplatin demonstrated higher antimetastatic activity compared with plain drug, indicating the usefulness of nanocarrier in treatment of metastasis (Gude et al 2002 ; Sant et al 2000 ). The market-available DOXIL® (pegylated doxorubicin liposomes) which is used in metastasis was not that much defined by clinical trials due to a poor understanding of its role in the prevention of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6 mice were injected with 0.1 million B16F10 cells in 0.1 ml of PBS through intravenous route by the tail vein (Sant et al 2000 ). One group received only B16F10 cells and served as a control.…”
Section: Methodsmentioning
confidence: 99%
“…PTX, widely used as a hemorheological agent in the treatment of peripheral vascular disease, was earlier shown to suppress lung metastasis formation by B16F10 melanoma [43] and NAC inhibits VEGF production in human melanoma cell lines [44], invasion of endothelial cells [45], and invasion of human bladder cancer cells through the suppression of MMP-9 [46]. ASP has been demonstrated to inhibit angiogenesis [47] and HGF-induced invasiveness of HepG2 human hepatoma cells [48].…”
Section: Suppression Of Metastasis By Nuclear Factor Kappab Inhibitormentioning
confidence: 99%